IDENTIFIKASI KANDUNGAN KARBON TERSIMPAN SEDIMEN MANGROVE KAPANEWON KRETEK, KABUPATEN BANTUL - Safitri, Antika Dila; Mulyanto, Djoko; Partoyo; Herlambang, Susila (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2025)
Mangrove forests can store four times more carbon than other tropical forests, mainly stored in the soil. This study aimed to evaluate the carbon content stored at two sediment depths (0-30 cm and 30-60 cm) with different vegetation density levels (very dense, medium, and sparse). The method used was a survey with purposive sampling and sampling using a 7.6 cm diameter PVC sediment corer. Parameters analysed included sediment texture, weight volume (BV), pH, salinity, and organic carbon content. The results showed that the denser the vegetation, the higher the stored carbon and the highest in the 30-60 cm depth zone, with a value of 184-403 tons/ha, while in the upper zone, 0-30 cm amounted to 29-210 tons/ha. In general, higher mangrove density levels had higher salinity, lower BV, but varying pH values with a range of neutral-slightly alkaline, and had a finer soil texture. The highest and lowest densities had salinities of (2.10-4.13 mS/cm) and (0.28-2.50 mS/cm), respectively, with BV values of 0.932 and 1.752 g/cm³.